2015
DOI: 10.1136/bmjdrc-2014-000044
|View full text |Cite
|
Sign up to set email alerts
|

Complication characteristics between young-onset type 2 versus type 1 diabetes in a UK population

Abstract: BackgroundIn the UK, the care of young people with diabetes has focused predominantly on type 1 diabetes (T1D). However, young-onset T2D has become increasingly prevalent. At present, it is unclear which type of diabetes represents the more adverse phenotype to develop complications. This study aims to determine the complication burden and its predictive factors in young-onset T2D compared with T1D.MethodsA cross-sectional study using a hospital diabetes register to identify patients with young-onset T2D and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 32 publications
8
64
2
Order By: Relevance
“…This result is similar to The National Diabetes Urban Survey (NUDS) conducted in India in 2000 which showed that more than 50% of diabetic cases developed T2DM before the age of 50 years [40]. Since the onset of T2DM is very early compared to other ethnic groups, complications and chronic risks of T2DM are set at an early years, cardiovascular risk [45][46][47], ischemic heart disease and neuropathy [46], other risks related with early onset of T2DM [48], obesity [49], clinical risk factor [50] agreement with many factors [51] etc. and therefore, mortality rate increases due to T2DM.…”
Section: Development Of Early Complicationssupporting
confidence: 72%
“…This result is similar to The National Diabetes Urban Survey (NUDS) conducted in India in 2000 which showed that more than 50% of diabetic cases developed T2DM before the age of 50 years [40]. Since the onset of T2DM is very early compared to other ethnic groups, complications and chronic risks of T2DM are set at an early years, cardiovascular risk [45][46][47], ischemic heart disease and neuropathy [46], other risks related with early onset of T2DM [48], obesity [49], clinical risk factor [50] agreement with many factors [51] etc. and therefore, mortality rate increases due to T2DM.…”
Section: Development Of Early Complicationssupporting
confidence: 72%
“…Our results collaborated with the results of Heidari and Rassoulinejad et al who reported dyslipidemia, smoking and hypertension were not associated with DR. 5 Song et al reported increased age, higher prevalence of obesity, hypertension, and dyslipidemia are significantly causing risk factors for diabetic retinopathy. 6 Ocular complications occur at higher BMI levels than other complications in both genders were reported by Gray and Picone et al 7 Obesity imposes diabetic patients to more severe DR due to inflammatory process. Both obesity and inflammation play a role in the development of endothelial impairment involved in diabetic retinopathy.…”
Section: Diabetic Retinopathy (Dr) and Risk Factorsmentioning
confidence: 79%
“…11 Song, reported neuropathy became significantly higher in T2DM after 20 years duration. 6 Distal symmetrical polyneuropathy shows a constant rise with duration reported by Orchard and Dorman et al 12 Ramachandran and Snehalatha et al showed that age and higher HbA1 had a significant association with neuropathy but hypertension was not associated with the complications of neuropathy. …”
Section: Diabetic Neuropathy (Dn)mentioning
confidence: 92%
“…patients with young-onset type 2 diabetes (age of onset ,40 years) (3)(4)(5)(6). However, the natural history of young patients with type 2 diabetes and resulting complications has not been well studied.…”
mentioning
confidence: 99%